2019
DOI: 10.4018/978-1-5225-7766-9.ch006
|View full text |Cite
|
Sign up to set email alerts
|

The Intelligence of E-CRM Applications and Approaches on Online Shopping Industry

Abstract: Today, most businesses are in continuous search of sophisticated tools and techniques to progressively grow their business. Therefore, the use of intelligence systems has found its pace in the global market. The intelligence systems has mostly affected the E-CRM as it is the most critical and central part for the growth of the business. The E-CRM approaches have enhanced drastically with an integration of the business intelligence systems and organizations are now diligently striving for excellence by gaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Regarding outer model results, indicators with loading factors < 0.80 are E-SQ3 (practicality), E-SQ5 (availability), ITSM2. 3 (smooth operation), ISSM3.1 (service responsiveness), and ISSM3.2 (service guarantees) with consecutive values 0.781, 0.793, 0.766, 0.752, and 0.771. All of these indicators represent three main constructs and IT governance turns out to have the highest value, meaning that online stores have understood and implemented it well based on company needs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding outer model results, indicators with loading factors < 0.80 are E-SQ3 (practicality), E-SQ5 (availability), ITSM2. 3 (smooth operation), ISSM3.1 (service responsiveness), and ISSM3.2 (service guarantees) with consecutive values 0.781, 0.793, 0.766, 0.752, and 0.771. All of these indicators represent three main constructs and IT governance turns out to have the highest value, meaning that online stores have understood and implemented it well based on company needs.…”
Section: Resultsmentioning
confidence: 99%
“…Online commerce communication is more effective, more interactive in terms of procurement and distribution of products based on customers' needs. Running the online stores excludes high operational costs and chances of increasing profit margins [3]. The shift of paradigm in businesses is from goods-based economy to IT service-based economy [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a different perspective, Ahmed, et al (2019); Pandey (2012) stated that CRM refers to a business process that leads to generation of revenue and optimization of profit during attaining customer satisfaction. It was found that it is very important for the success of CRM system to be processed and oriented at a strategic level that connects the informational, operational as well as the organizational factors of CRM.…”
Section: Customer Relationship Management (Crm) and Satisfactionmentioning
confidence: 99%
“…Mudah menjalin kerjasama dengan mitra bisnis dalam pengadaan dan mendistribusikan produk dan jasa secara langsung tanpa perantara. Kenyataan ini jelas akan menurunkan biaya operasional dan meningkatkan marjin usaha [4]. Kondisi ini merupakan faktor penting bagi setiap lapisan masyarakat untuk ikut serta menawarkan produk dan jasa melalui kepemilikan usaha bisnis pemasaran online [5].…”
Section: Pendahuluanunclassified